A Field Guide to the Southeast Coast & Gulf of Mexico: Coastal Habitats, Seabirds, Marine Mammals, Fish, & Other Wildlife - Proctor, Noble S. (Yale University Press, 2011)
"This superb book, with its unique focus on the entire marine coastal environment, is the most comprehensive and up-to-date field guide available on the southeastern Atlantic Coast and the Gulf Coast. Not just for beachgoers, the book is essential for birders, whale watchers, fishers, boaters, scuba divers and snorkelers, and shoreline visitors" –Publisher description.
Keywords: Atlantic Coast (South Atlantic States); Coastal animals; Guidebooks; Guidebooks; Atlantic Coast (South Atlantic States); Guidebooks; Coastal ecology; Guidebooks; Marine ecology; Guidebooks; Mexico; Gulf of; Gulf States; Identification; Coastal animals; Identification; Coastal ecology; Identification; Marine animals; Mexico; Gulf of; South Atlantic States; dept.bio; faculty_collection

Variation in seed dormancy quantitative Trait Loci in arabidopsis thaliana originating from one site - Silady, R.A.; Effgen, S.; Koornneef, M.; Reymond, M. (PLoS ONE, 2011)
A Quantitative Trait Locus (QTL) analysis was performed using two novel Recombinant Inbred Line (RIL) populations, derived from the progeny between two Arabidopsis thaliana genotypes collected at the same site in Kyoto (Japan) crossed with the reference laboratory strain Landsberg erecta (Ler). We used these two RIL populations to determine the genetic basis of seed dormancy and flowering time, which are assumed to be the main traits controlling life history variation in Arabidopsis. The analysis revealed quantitative variation for seed dormancy that is associated with allelic variation at the seed dormancy QTL DOG1 (for Delay Of Germination 1) in one population and at DOG6 in both. These DOG QTL have been previously identified using mapping populations derived from accessions collected at different sites around the world. Genetic variation within a population may enhance its ability to respond accurately to variation within and between seasons. In contrast, variation for flowering time, which also segregated within each mapping population, is mainly governed by the same QTL. © 2011 Silady et al.
13 citations (Crossref) [2023-10-31]
Keywords: Arabidopsis; Arabidopsis Proteins; Arabidopsis protein; Arabidopsis thaliana; DOG1 protein; Arabidopsis; Delay Of Germination 1 gene; Delay Of Germination 6 gene; Japan; Plants; Genetically Modified; Quantitative Trait Loci; Seed Dormancy; article; controlled study; dept.bio; flowering; gene mapping; genetic variability; genetics; genotype; nonhuman; peer-reviewed; physiology; plant chromosome; plant gene; quantitative trait locus; recombinant inbred strain; seed dormancy; transgenic plant

A new species of Acentrella Bengtsson (Ephemeroptera: Baetidae) from New York and New England (USA), redescription of the nymph of A. parvula (McDunnough), and key to known adult males of Nearctic Acentrella - Burian, Steven K; Myers, Luke W (Aquatic Insects, 2011)
A new species Acentrella rallatoma (type locality: Connetquot River, Oakdale, NY, USA) is described from nymphs and reared adults. Additional specimens were studied from southeastern New York, southeastern New Hampshire, coastal Connecticut, and Martha's Vineyard, MA, USA. Nymphs can be separated from those of other Nearctic species by: scraper-like outer incisors of mandibles, cerci alternately banded from bases to tips, and row of robust bristle-like setae (with modified tips) on dorsal edge of femora. Male imagos can be separated from those that lack hind wings by: distinctive colour pattern of abdominal terga, and genitalia with pigmented sclerotised penes cover. Comparative analysis of A. rallatoma with other Nearctic species revealed a lack of comparative data on nymphs of its presumptive sister species A. parvula. To facilitate future studies of this group, the nymph of A. parvula is redescribed and regional differences are discussed. Abdominal colour patterns of A. parvula that vary over its range from Florida, USA to Labrador, Canada are illustrated. Problems concerning genus-level diagnostic characters for Acentrella nymphs and adults are discussed to facilitate placement of future taxa. To complement existing keys to Nearctic nymphs of Acentrella a provisional key to the known adult males is given. © 2011 Copyright Taylor and Francis Group, LLC.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/062-428-772-783-321 tex.type: [object Object]
Keywords: A. parvula; Acentrella; Acentrella parvula; Baetidae; Ephemeroptera; dept.bio; new species

Effect of increased extracellular Ca++ on microvesicle production and tumor spheroid formation - Crawford, Sarah; Diamond, Deanna; Brustolon, Laura; Penarreta, Rafaela (Cancer microenvironment : official journal of the International Cancer Microenvironment Society, 2011)
Research on the composition of the tumor micro-environment has demonstrated that membrane delimited microvesicles are shed from many types of malignant tumors, in the peripheral blood of cancer patients as well as in culture media of tumor cells propagated in vitro (Ginestra et al. Anticancer Res 18:3433-3437, 1998). Their documented effects involve the activation of signal transduction pathways by cellular cross-talk that are associated with epigenetic mechanisms that may be important in tumor progression, metastasis, and the activation of angiogenesis (Distler et al. Arthritis Rheum 52:3337-3348, 2005). Live cell imaging microscopic studies conducted in our laboratory of the formation of solid tumor spheroids in vitro show that the shedding of microvesicular structures from tumor cells occurs during this process. The observed properties of the tumor microvesicles suggest a role in solid tumor formation and intercellular communication. The tumor associated microvesicles were shown to be non-apoptotic based on the absence of fluorescent nuclear staining by acridine orange/ethidium bromide staining. Increased concentration of extracellular Ca(++) [5-20 mM] resulted in an increase in the production of tumor-derived microvesicles and also to result in the formation of tumor spheroids whose size was considerably smaller than controls. Increased extracellular [Ca(++)] was also observed to induce the rapid dissociation of solid tumor spheroids to smaller cell aggregates in the absence of significant apoptosis.
19 citations (Crossref) [2023-10-31] Place: Netherlands Crawford, Sarah. Cancer Biology Research Laboratory, Biology Department, Southern Connecticut State University, Jennings Hall 219, 501 Crescent Street, New Haven, CT 06515 USA.
Keywords: Extracellular Ca++; Live cell imaging; Multicellular tumor spheroid; Tumor associated microvesicle; acridine orange; angiogenesis; apoptosis; article; breast carcinoma; calcium ion; cancer cell culture; cell aggregation; cell nucleus; concentration (parameters); controlled study; cytochemistry; dept.bio; epigenetics; ethidium bromide; extracellular calcium; glioblastoma; human; human cell; in vitro study; membrane vesicle; metastasis potential; microscopy; molecular interaction; osteosarcoma; priority journal; signal transduction; tumor growth; tumor microenvironment; tumor spheroid; tumor vascularization